Art : over 2,500 works from cave to contemporary - King, Ross, 1962- (New York, N.Y. : DK Pub., 2008)
Within each time period, provides examples of significant works in painting, sculpture, drawing and other media. Highlights themes that were important at various times such as nudes, landscape, still life, and love. Includes brief biographies of some artists and a "closer look" in depth for the most significant works.
Looking at art -- Prehistory to 1400 CE -- 15th and 16th centuries -- 17th and 18th centuries -- 19th century -- Early 20th century -- 1945 onward.
Includes index.
Keywords: Art -- History; Art appreciation; History